Extracellular vesicles from normal tissues orchestrate the homeostasis of macrophages and attenuate inflammatory injury of sepsis - Xinyu Ge; Qingshu Meng; Xuan Liu; Shanshan Shi; Xuedi Geng; Enhao Wang; Mimi Li; Xiaoxue Ma; Fang Lin; Qianqian Zhang; Yinzhen Li; Lunxian Tang; et al. (Wiley, 2024)
Abstract Extracellular vesicles (EVs) exist throughout our bodies. We recently revealed the important role of intracardiac EVs induced by myocardial ischemia/reperfusion on cardiac injury and dysfunction. However, the role of EVs isolated from normal tissues remains unclear. Here we found that EVs, derived from murine heart, lung, liver and kidney have similar effects on macrophages and regulate the inflammation, chemotaxis, and phagocytosis of macrophages. Interestingly, EV‐treated macrophages showed LPS resistance with reduced expressions of inflammatory cytokines and enhanced phagocytic activity. Furthermore, we demonstrated that the protein content in EVs contributed to the activation of inflammation, while the RNA component mainly limited the excessive inflammatory response of macrophages to LPS. The enrichment of miRNAs, including miR‐148a‐3p, miR‐1a‐3p and miR‐143‐3p was confirmed in tissue EVs. These EV‐enriched miRNAs contributed to the inflammation remission in LPS induced macrophages through multiple pathways, including STAT3, P65 and SAPK/JNK. Moreover, administration of both EVs and EV‐educated macrophages attenuated septic injury and cytokine storm in murine CLP models. Taken together, the present study disclosed that EVs from normal tissues can orchestrate the homeostasis of macrophages and attenuate inflammatory injury of sepsis. Therefore, tissue derived EVs or their derivatives may serve as potential therapeutic strategies in inflammatory diseases.